2023
DOI: 10.1002/1873-3468.14755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sound energy on proteins and their complexes

Anna Kozell,
Aleksei Solomonov,
Ulyana Shimanovich

Abstract: Mechanical energy in the form of ultrasound, and protein complexes intuitively have been considered as two distinct unrelated topics. However, in the past few years, increasingly more attention has been paid to the ability of ultrasound to induce chemical modifications on protein molecules that further change protein‐protein interaction and protein self‐assembling behavior. Despite efforts to decipher the exact structure and the behavior‐modifying effects of ultrasound on proteins, our current understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Studies have delved into understanding the influence of external fields, such as sound energy, on amyloid‐like assemblies. Our recent studies [47,77] that are also summed up in, [78] it was demonstrated that ultrasound can either transform lysozyme amyloid structures into non‐amyloidogenic forms by disrupting their β ‐sheet structure (Figure 5, panel IV) or lead to fibrillar structures formation. This results in aggregates with intriguing mechanical properties and shapes.…”
Section: Recent Breakthroughs In Protein Biomaterialsmentioning
confidence: 90%
“…Studies have delved into understanding the influence of external fields, such as sound energy, on amyloid‐like assemblies. Our recent studies [47,77] that are also summed up in, [78] it was demonstrated that ultrasound can either transform lysozyme amyloid structures into non‐amyloidogenic forms by disrupting their β ‐sheet structure (Figure 5, panel IV) or lead to fibrillar structures formation. This results in aggregates with intriguing mechanical properties and shapes.…”
Section: Recent Breakthroughs In Protein Biomaterialsmentioning
confidence: 90%
“…The influence of ultrasound is intricately linked to the disruption of essential intermolecular interactions such as Van der Waals forces and hydrogen bonds (Kozell, Solomonov, & Shimanovich, 2023).Guerra-Almonacid et al ( 2019) illustrated that ultrasound pretreatment amplifies the Alcalase enzyme's activity, attributed to ultrasoundgenerated forces capable of breaking protein molecule chains. Previous studies have explored ultrasound's potential to deactivate enzymes like polyphenol oxidase and peroxidase, mitigating the risk of browning in juices (Qureshi et al, 2020).…”
Section: Enzyme Activity and Food Digestibilitymentioning
confidence: 99%